Балансування напруги модульного накопичувача енергії джерела живлення для контактного мікрозварювання - Kozhushko, Yu. V.; Bondarenko, O. F. (PE "Politekhperiodika", Book and Journal Publishers, 2017)
Micro resistance welding is one of the most effective ways to obtain permanent joints of metal parts. The quality of welded joints strongly depends on the characteristics of the power supply of welding equipment. The power supplies for micro resistance welding based on Energy Storage topology have a softer impact on the network than the ones based on Direct Energy topology. The use of supercapacitors for Energy Storage type power supplies makes it possible to reduce the dimensions of welding equipment and to improve its technical parameters. However, the feature of the supercapacitors is low value of the nominal voltage, which usually does not exceed 3 V. To provide higher voltage, the modules of supercapacitors connected in series are designed. In order to extend the lifetime of such modules, a voltage balancing system is required.A circuit for balancing the voltage of a modular supercapacitor energy storage of a power supply for micro resistance welding is proposed. The fragments of calculation of control units of a supercapacitor module cell are given. The simulation of the balancing circuit operation is carried out and time charts of the supercapacitor charge process are obtained. The operability and effectiveness of the proposed solution is confirmed. The advantage of the proposed circuit is the possibility of obtaining the high efficiency because of returning the excessive energy of the module cell back into the power supply.